2018
DOI: 10.2174/0929866524666170621094921
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Humoral and Cellular Immune Responses in Mice by Multiepitope Vaccines Composing of Both T and B Lymphocyte Epitopes of MAGE-A3 which are Recombined into HBcAg

Abstract: Our results indicated MIR in HBcAg presenting platform could present MAGE-A3 multiepitopes efficiently and induced significant humoral or cellular immunity. The immune strategy based on multiepitopeimmunization could have potential for preventing or controlling MAGE-A3 associated malignant disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…However, the two largest phase III clinical trials targeting MAGEA3 immunotherapeutic as an adjuvant therapy for stage III melanoma and nonsmall cell lung cancer failed ( 26 , 27 ), which is stagnating the progress of immunotherapeutic, and research on MAGEA3 also have declined. In our previous study, we have identified epitopes from MAGEA3 protein and found that patients with gastric cancer had higher reactivity to these epitopes ( 28 ); we also found that MAGEA3 multiepitope vaccine can induce humoral and cellular immune responses in mice ( 29 ), so we still believe MAGEA3 is an important target for GC diagnosis and immunotherapy. In this research, we analyzed the relationship between MAGEA3 and gastric cancer patients’ prognosis through the Cancer Genome Atlas (TCGA) database and investigated the effect of MAGEA3 expression on immune cell infiltration, further screening out MAGEA3-related proteins and interacting miRNA.…”
Section: Introductionmentioning
confidence: 93%
“…However, the two largest phase III clinical trials targeting MAGEA3 immunotherapeutic as an adjuvant therapy for stage III melanoma and nonsmall cell lung cancer failed ( 26 , 27 ), which is stagnating the progress of immunotherapeutic, and research on MAGEA3 also have declined. In our previous study, we have identified epitopes from MAGEA3 protein and found that patients with gastric cancer had higher reactivity to these epitopes ( 28 ); we also found that MAGEA3 multiepitope vaccine can induce humoral and cellular immune responses in mice ( 29 ), so we still believe MAGEA3 is an important target for GC diagnosis and immunotherapy. In this research, we analyzed the relationship between MAGEA3 and gastric cancer patients’ prognosis through the Cancer Genome Atlas (TCGA) database and investigated the effect of MAGEA3 expression on immune cell infiltration, further screening out MAGEA3-related proteins and interacting miRNA.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, the autoantigen molecules displayed by HBcAg VLPs can escape immune tolerance and produce specific auto-antibodies (Long et al, 2014). Due to these advantages, the HBc is often used as a powerful carrier protein and built-in adjuvant to display exogenous epitopes (Chen et al, 2017; Jiang et al, 2017; Roose et al, 2013; Liang et al, 2018). In general, researchers will insert pathogen epitopes into the HBcAg major immunogenic region (MIR; HBcAg aa 78–82 in the spike tip of HBV), which does not affect the self-assembly of the fusion protein into VLP NPs, to generate immune activation; therefore, antigen epitopes will be presented on the surface of the particles (Wang et al, 2017a; Chen et al, 2017) (Fig.…”
Section: Virus-like Particles As Built-in Adjuvant Platformsmentioning
confidence: 99%
“…Therefore, a built-in adjuvant exhibiting both the functions of a transmission system and a traditional adjuvant, is constructed within the vaccine to improve the immunogenicity of epitope peptides by stimulating the innate immune response required for an adaptive immune response. To achieve this goal, the epitopes are regularly fused with adjuvant proteins (e.g., toll-like receptor (TLR) ligands and proteins that can spontaneously assemble into virus-like particles (VLPs)) or displayed on the surface of some particular biomaterials (e.g., liposomes, gold nanoparticles, and poly(lactic- co -glycolic acid) (PLGA)) and the immunogenicity of the epitopes are significantly increased by this immune complex (Chen et al, 2017; Rueda et al, 2017; Kitaoka et al, 2017; Karuturi et al, 2017). This review primarily introduces the methods for applying built-in adjuvants in the design of epitope-based vaccines, including a few new delivery systems (e.g., dendrimers, self-assembled peptide nanoparticles (SAPNs), and hyperbranched polyglycerol (hbPG)) (Busseron et al, 2013; Glaffig et al, 2015; Indelicato, Burkhard & Twarock, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the autoantigen molecules displayed by HBcAg VLPs can escape immune tolerance and produce specific auto-antibodies (Long et al, 2014). Due to these advantages, the HBc is often used as a powerful carrier protein and built-in adjuvant to display exogenous epitopes (Chen et al, 2017;Jiang et al, 2017;Roose et al, 2013;Liang et al, 2018).…”
Section: Salmonella Porinmentioning
confidence: 99%
“…In general, researchers will insert pathogen epitopes into the HBcAg major immunogenic region (MIR; HBcAg aa 78 -82 in the spike tip of HBV), which does not affect the self-assembly of the fusion protein into VLP nanoparticles, to generate immune activation; therefore, antigen epitopes will be presented on the surface of the particles Chen et al, 2017) (Fig. 4A).…”
Section: Virus-like Particles (Vlps) As Built-in Adjuvantmentioning
confidence: 99%